Aergia and Pasithea: toward a cosmogonic understanding of laziness in Ancient Greece (2021)
The present study aims to justify how laziness constitutes an intrinsic part of the human substance within cosmogony in Ancient Greece. To do so, the paper is divided into three parts. First, a brief explanation of what hard work implies is offered from its mythological personification: Horme. Second, skholè i s regarded as a concept in which laziness and contemplation converge in the direction of a reflective capacity based on inaction. Third, it is argued that Aergia and Pasithea are goddesses that provide the basis for considering laziness as an ontological category within human beings’ understanding of themselves. The latter, inasmuch as they are deities that are found within the human constitution before the skholè, which places them as fundamental for the study of leisure in Ancient Times.